The Use Superordinate Concept in The Meaning of speech - Dicky Widiya Perkasa; Iman Santoso (PROJECT (Professional Journal of English Education), 2019)
Words have been existed since hundreds of years ago the implicit meaning of a words can indicate an expression of someone Through human words can communicate with various kinds of meanings in their conversation, in the concept of writing the researcher will explain a concept of superordinate which as a form of word level the highest which has the earliest meaning of each word, The good thing that can be learned in this superordinate concept is that the meaning of the word will not become complicated, for example "The fish is very ferocious", then what fish does it mean that might be sharks or dolphins, in fact sharks are wild fish, but fish dolphins are not fierce, from which the superordinate has not been able to represent the above words so that in the form of the next two concepts which further pursing the word "fish" above into "The shark is very ferocious" the shark refer to the Basic concept and then it can be more specific from Subordinate to be like this "The white shark is very fierce" (white shark) is subordinate. In another case why the researcher takes the concept from this superordinate is to explain that a meaning in the word has owned level and then the words will not always have the same meaning in delivering their purpose, regardless of the daily conversation pretty much people used "Basic and Subordinate" due the meaning is more referring and precise.